The consequences of household composition and household change for Indigenous health: evidence from eight waves of the Longitudinal Study of Indigenous Children (LSIC) - Hewitt, Belinda; Walter, Maggie (My University, 2021)
Households are important health contexts, providing social, emotional, financial and material support, but little is known about the role of household composition in the social etiology of Indigenous health. Our research is framed by an Indigenous standpoint, using eight waves of data from the Longitudinal Study of Indigenous Children. We investigated whether household composition and change in household composition were associated with the self-reported general health of Indigenous children and their mothers, adjusting for socioeconomic, household structure and social support factors. Our measure of household composition comprised eight groups differentiating lone and couple parents, living with and without other children and adults. Study children in couple households with other children and adults were 16% less likely to have excellent health and mothers in these same households were 7% less likely to report excellent health than children and mothers in couple households. We find little evidence that mothers in lone parent households have poorer health than mothers in couple households, after adjustment for covariates. Change in household composition was positively associated with health for both children and mothers. The results caution against presuming a direct translatability of research findings from non-Indigenous to Indigenous Peoples.
Journal of Sociology
Keywords: Families and relationships; Health and wellbeing